Debt Sustainability Assessment of Regional Budgets - E. G. Kiseleva (Финансы: теория и практика, 2022)
The aim of the paper is to assess the debt sustainability of the budget system of the regions of the Northwestern Federal District (NWFD) of Russia and establish differentiated values of the budget constraints. The author uses methods of comparison and grouping, correlation and cluster analysis. The author’s methodology based on the methods of multivariate statistical analysis made it possible to include indicators that have the nature of leading indicators in the assessment, evaluate the integral indicator of debt sustainability, and determine the limit values of these indicators. Approbation of the author’s methodology for assessing the debt sustainability of the budget system on the statistics of the NWFD regions allowed dividing the regions into three clusters according to the types of debt sustainability and determining the threshold values of indicators for each cluster. The research results substantiate the need to reduce the high debt burden for 70% of the NWFD regions. The results indicate that the regions with a high level of debt sustainability include St. Petersburg, Leningrad and Kaliningrad regions. The integral indicator of debt sustainability of these regions is greater than one and the regions are well grouped according to six indicators of debt sustainability into a group that is homogeneous in terms of characteristics. The Republic of Komi, the Republic of Karelia, and the Arkhangelsk and Pskov regions have a low level of debt sustainability: the standard limiting values for the “debt-to-GRP ratio” indicator of the regions is less than 5%, and the “debt-to-revenue ratio” indicator — less than 42%, the value of all indicators of debt sustainability exceeds the values of the cluster centroids. For these regions, the author recommends pursuing a targeted budget policy with a mandatory debt reduction to the level of threshold values for the indicators of the regions of this cluster. The paper concludes that it is necessary to reduce the debt burden of most regions of the NWFD, as well as to establish differentiated values of budget constraint on public debt, taking into account the indicators of socio-economic development of these regions.